PENGARUH KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN TRANSPORTASI DAN LOGISTIK - Tamini, Komang Eprianti; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p06, 2024)
This research is useful for examining the impact of financial decisions, investment and profitability on company value. The subjects of this research are companies in the transportation and logistics sector listed on the IDX for the 2020–2022 period. This research has theoretical and practical consequences because it can offer empirical and practical insight into how funding, investment and profitability decisions have an impact on company value. These insights can then be used as a basis for further research. The sample in this research was a total of 24 companies, utilizing saturated sampling steps. The data analysis technique used, namely multiple linear regression analysis, is the analysis method used in this research. Based on research findings, decisions regarding funding have a positive impact on company value, but decisions regarding investment do not have this effect. Profitability, on the other hand, has a positive impact on company value. Suggestions for future research are to continue this research by including additional variables such as liquidity, dividend policy, and asset growth into the research model. In order to get more comprehensive results, the author can also increase research time and expand the research object.